Efek Antijamur Ekstrak Daun Selasih Liar (Ocimum gratissimum) pada Fusarium oxysporum f. sp. cepae dan Alternaria porri pada Bawang Merah The antifungal properties of clove basil (Ocimum gratissimum L.) extract on Fusarium oxysporum f. sp. Cepae and Alter - Bambang Nugroho; Warmanti Mildaryani (Jurnal Ilmu Pertanian Indonesia, 2024)
The antifungal properties of clove basil (Ocimum gratissimum L.) extract on Fusarium oxysporum f. sp. Cepae and Alternaria porri were evaluated in vitro and in vivo. Thirty grams of the clove basil sterilized leaves were mashed in a sterile mortar, soaked for 24 hr in 100 mL of 96% ethanol as an extractant. The extract was filtered through sterile Whatman No. 1 filter paper and stored at 4°C for subsequent use. Three different concentrations (5, 10, and 15%) were applied using the poisoned food technique. A 4-mm diameter mycelial disc of each tested fungus was inoculated on each amended agar plate. Daily radial growth was recorded for 7 days. For the in vivo test, two different concentrations (15% and 20%) were used. No spray and mancozeb spraying were used as controls. Seed bulbs of shallots were planted in a 25 cm x 25 cm polybag and allowed to be naturally infected by Alternaria porri. The clove basil leaf extract and mancozeb were sprayed onto the plants once a week, starting when the first symptom of the purple blotch disease appeared. The results showed that clove basil leaf extract had good efficacy in inhibiting F. Oxysporum f. sp. Cepae and A. Porri in vitro, with a growth inhibition up to 55%. The extract can also reduce the disease intensity of purple blotch with an infection rate of 0.029, indicating that it has the potential to be developed as a botanical fungicide. Keywords: antifungal effect, Alternaria porri, clove basil, Fusarium oxysporum f. sp. cepae, leaf extract